2012
DOI: 10.1111/j.1471-0307.2012.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigment from red fermented rice as colouring agent for stirred skimmed milk yoghurts

Abstract: Yoghurt is one of the most popular fermented milk products worldwide and is becoming more and more popular in China. In this study, the pigment of red fermented rice (RFR) by Monascus spp., which have been used as natural edible pigments in Asian countries for more than a thousand years, were applied to colour yoghurts. The colour stabilities, physicochemical characters and organoleptic qualities of the yoghurts containing 0 (control), 1.25, 2.5 and 5.0 pigment units/mL of milk, were measured after 1, 4, 7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…This increase of L* indicates possible degradation or oxidation of the color pigments and therefore lightness of the colorant is increased. This is in agreement with several studies such as red rice pigmented yogurt ( Chen, Lv, Du, & Chen, 2012 ) and fruity yogurt ( Pires et al, 2018 ). In contrast to our observations, grape incorporated kefir ( Montibeller et al, 2018 ), which showed a decrease in L* value over time.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This increase of L* indicates possible degradation or oxidation of the color pigments and therefore lightness of the colorant is increased. This is in agreement with several studies such as red rice pigmented yogurt ( Chen, Lv, Du, & Chen, 2012 ) and fruity yogurt ( Pires et al, 2018 ). In contrast to our observations, grape incorporated kefir ( Montibeller et al, 2018 ), which showed a decrease in L* value over time.…”
Section: Resultssupporting
confidence: 94%
“…However, all of the evaluated attributes showed significance on the 14th day. In agreement, Chen et al (2012) have also, gain insignificant appearance and texture in their red rice pigmented yogurt at 2 weeks under 4 °C.…”
Section: Resultssupporting
confidence: 63%
“…RYR-derived pigments possess hypolipidemic effects (Zhou et al, 2019) as well as anti-cancer (Xu et al, 2017), anti-fatigue (Chen, 2004), and anti-inflammatory (Hsu et al, 2010) activities. In addition, RYR pigments can be used to color yogurt red (Chen et al, 2012b). The chemical structures of these molecules are shown in Figures 3 and 4 .…”
Section: Chemistrymentioning
confidence: 99%
“…However, all the organoleptic properties slightly decreased during the storage of RYRF yoghurts. The decline in organoleptic properties during storage might be related to the associated decrease in pH values [19][20][21].…”
Section: Organoleptic Properties Of Ryrf Yoghurtsmentioning
confidence: 99%